Preparation and Fire-Resistant Properties of Fly Ash Floating Beads/Epoxy Resin Coatings - Wang, Qingping; Wang, Hui; Min, Fanfei; Zhu, Jinbo (Asian Journal of Chemistry, 2014)
The surface of fly ash floating beads were modified by using silane coupling agent and the fly ash floating beads/epoxy resin fire-resistant coatings were prepared through mixing method. The surface composition and micro-morphology of modified fly ash floating beads were studied by FT-IR and SEM. The fire-resistant properties of fire-resistant coatings modified by fly ash floating beads were tested through combustion method. The influence of the content of fly ash floating beads was discussed and combining with changes of the opposite surface temperature. The fire-resistant mechanism of fly ash floating beads was also proposed. The results showed that the characteristic functional groups of silane coupling agent appeared on the surface of modified fly ash floating beads, the surface grafting phenomenon was obvious. With the increase of the content of fly ash floating beads, the fire-resistant properties increased firstly and then decreased. When the content of fly ash floating beads was 5 %, it could make the fire-resistant properties of fire-resistant coatings to achieve the best.